2021
DOI: 10.1007/s00406-021-01306-3
|View full text |Cite
|
Sign up to set email alerts
|

P2X7R antagonists in chronic stress-based depression models: a review

Abstract: Depression affects around 320 million people worldwide. Growing evidence proposes the immune system to be the core interface between psychosocial stress and the neurobiological and behavioural features of depression. Many studies have identified purinergic signalling via the P2X7 receptor (P2X7R) to be of great importance in depression genesis yet only a few have evaluated P2X7R antagonists in chronic stress-based depression models. This review summarizes their findings and analyses their methodology. The four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 178 publications
(294 reference statements)
1
15
0
Order By: Relevance
“…In the following experiments, we compared the current amplitudes induced by NMDA (100 µM) and Bz-ATP (300, 1000 µM), in very young (12)(13)(14) and young (23)(24)(25) day old rat astrocytes. Interestingly, both NMDA and Bz-ATP showed effects that depended on the age of the animals.…”
Section: Immediate Modulation Of Astrocytic Functions In the Hippocam...mentioning
confidence: 99%
See 1 more Smart Citation
“…In the following experiments, we compared the current amplitudes induced by NMDA (100 µM) and Bz-ATP (300, 1000 µM), in very young (12)(13)(14) and young (23)(24)(25) day old rat astrocytes. Interestingly, both NMDA and Bz-ATP showed effects that depended on the age of the animals.…”
Section: Immediate Modulation Of Astrocytic Functions In the Hippocam...mentioning
confidence: 99%
“…(2) The genetic deletion of P2X7Rs in mice results in decreased behavioral despair and, consequently, reduced immobility in FST and TST, indicating an antidepressive phenotype [17,18]. (3) Especially, chronic stress models in rodents have convincingly born out the participation of P2X7Rs in depressive-like behaviors, in combination with immune changes (NLRP3 inflammasome assembly and activation, IL-1β release, microglia activation) and neuroplasticity impairments [19][20][21][22][23] (see also Section 3). In all of these studies, unpredictable, chronic mild stress or unpredictable, chronic stress was applied for the duration of a few weeks, and for the second half of each stress paradigm a P2X7R antagonist (Brilliant Blue G, A-438079, A-804598) was administered.…”
Section: Introductionmentioning
confidence: 99%
“…Once activated, P2X7R adopts an open conformation, allowing K + efflux and Na + and Ca 2+ influx ( Habermacher et al, 2016 ; Di Virgilio et al, 2018 ), triggering the assembly of the intracellular NLR family pyrin domain containing 3 (NLRP3) inflammasome and subsequent activation of caspase-1. This stimulates cell metabolism via glycolysis and upregulation of oxidative phosphorylation and causes IL-1β, IL-6, TNFα, and IL-18 release, eliciting a neuroinflammatory response ( Di Virgilio et al, 2017 ; von Muecke-Heim et al, 2021 ). P2X7R activation also potentiates the innate immune response by inducing proliferation, recruitment and activation of microglia, macrophages, and lymphocytes ( Dubyak, 2012 ; Monif et al, 2016 ; Colonna and Butovsky, 2017 ).…”
Section: General Characteristics Of P2x7rmentioning
confidence: 99%
“…Translational research in rodents has shown that chronic stress causes extracellular ATP increase and P2X7R activation in the brain, which results in depressive-like behavior and impaired neuroplasticity ( Iwata et al, 2016 ; Wohleb et al, 2016 ; Metzger et al, 2017b ; von Muecke-Heim et al, 2021 ). Vice versa, blockage along the P2X7R -NLRP3-IL-1β cascade has been shown to promote stress resilience with microglia and monocytes playing an important part ( Schiweck et al, 2020 ; von Muecke-Heim et al, 2021 ). These studies point out P2X7R’s signaling role as an important interface between chronic stress and the behavioral features of clinical depression.…”
Section: P2x7r and Psychiatric Disordersmentioning
confidence: 99%
See 1 more Smart Citation